2012
DOI: 10.1007/s11665-012-0150-2
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue-Life Computational Analysis for the Self-Expanding Endovascular Nitinol Stents

Abstract: Self-expanding endovascular stents made of Nitinol (a Ni-Ti intermetallic compound possessing superelastic and shape-memory properties) are being widely used to treat a common circulatory problem in which narrowed arteries, primarily due to fatty deposits, hamper blood flow to the extremities (the problem commonly referred to as ''peripheral artery disease''). The stents of this type unfortunately occasionally fail structurally (and, in turn, functionally) rendering the stenting procedure ineffective. The fail… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 29 publications
(22 reference statements)
0
7
0
Order By: Relevance
“…Designing Nitinol devices against fatigue fracture not only demands an understanding of in-service loads, but of how the device's complex thermo-mechanical history affects its material level fatigue behavior. While numerous computational (Grujicic et al, 2012;Kumar et al, 2013;Rebelo et al, 2009) and some experimental studies (Pelton, 2011;Pelton et al, 2008) of device-level fatigue have incorporated crimping and deployment into the investigational protocol, few studies have clearly examined how this pre-strain cycle impacts overall fatigue properties. Schlun et al subjected pseudoelastic NiTi to an 8% tensile pre-strain and examined the evolution of the cyclic strain-stress behavior at 0.2% and 1.2% strain amplitude and 2% mean strain for 100 cycles (Schlun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Designing Nitinol devices against fatigue fracture not only demands an understanding of in-service loads, but of how the device's complex thermo-mechanical history affects its material level fatigue behavior. While numerous computational (Grujicic et al, 2012;Kumar et al, 2013;Rebelo et al, 2009) and some experimental studies (Pelton, 2011;Pelton et al, 2008) of device-level fatigue have incorporated crimping and deployment into the investigational protocol, few studies have clearly examined how this pre-strain cycle impacts overall fatigue properties. Schlun et al subjected pseudoelastic NiTi to an 8% tensile pre-strain and examined the evolution of the cyclic strain-stress behavior at 0.2% and 1.2% strain amplitude and 2% mean strain for 100 cycles (Schlun et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…After simulations (Steps 1–3) on stent manufacturing and deployment, a ±3% stent diameter oscillation was applied to simulate the pulsatile motion of the blood vessel. For the self-expanding stent, modified strain-based Goodman fatigue life analysis was used due to the unique properties of nitinol [ 27 , 28 , 44 , 49 , 50 , 51 ]. According to that analysis, fatigue failure occurs if the strain state within a stent satisfies the following relation: where ε a is the strain amplitude applied to the device, ε e is the material endurance limit, ε m is the mean strain applied to the device, and ε u is the material ultimate strain.…”
Section: Methodsmentioning
confidence: 99%
“…They concluded that the most critical parameter for the equivalent plastic strain and the expansion recoil was the crown radius. Grujicic et al [13] investigated the fatigue-controlled service life of the selfexpanding nitinol vascular stents. Praveen Kumar et al [14] provided a simple, fast, and costeffective tool to quantitatively determine the fatigue resistance of stent components.…”
Section: Materials Aspectsmentioning
confidence: 99%